Studi Pemasaran Bawang Merah (Allium ascalonicum L.) Menggunakan Sistem Tebasan di Desa Nglinggo Kecamatan Gondang Kabupaten Nganjuk - Nopitasari, Santi; Andajani, Wiwiek; Sidhi, Eko Yuliarsha; Pamujiati, Agustia Dwi (Jurnal Ilmiah Pertanian Nasional, 2024)
Shallots are used as a spice and spice; they are also used as traditional medicine ingredients and play a role in helping increase people's income in national development, one of which is the shallot plant. This research aims to determine the costs, income, and feasibility of shallot farming using the slash system in Nglinggo Village, Gondang District, Nganjuk Regency. This research was carried out purposively in Nglinggo village, Gondang district, Nganjuk district. This location was chosen because it is one of the centers for developing shallot farming. The sampling method used in this research was census (saturated sampling). Based on the survey results and these criteria, the number of farmers was 30 respondents. The types of data used in this research are primary and secondary. The data analysis methods include farming costs, revenue analysis, income analysis, R/C ratio, and profitability analysis. The results of research on the analysis of shallot farming using the slash marketing system showed that the average total production cost for shallot farming is IDR 88,109,666.7/Ha, the total revenue from shallot farming is IDR 128,313,365/Ha, the average shallot farming income is IDR 40,203,698/Ha. The R/C Ratio is 1.46, and profitability is 15.2%.   Salah satu bumbu yang sering digunakan adalah bawang merah. Bawang merah juga bermanfaat untuk obat tradisional dan berperan dalam peningkatan pendapatan masyarakat. Riset ini bertujuan untuk mengetahui biaya dan pendapatan serta pemasaran bawang merah dengan sistem tebasan di Desa Nglinggo Kecamatan Gondang Kabupaten Nganjuk. Riset ini dilaksanakan secara sengaja di Desa Nglinggo karena daerah tersebut salah satu sentral pengembangan usahatani bawang merah. Metode sensus digunakan untuk pengambilan sampel. Berdasarkan hasil survei dan juga kriteria tersebut, maka jumlah petani adalah 30 responden. Jenis Data utama dan data tambahan diperlukan pada riset ini. Metode analisis data yang dilakukan antara lain biaya usahatani, pendapatan, penerimaan, R/C Ratio serta rentabilitas. Hasil riset tentang analisis usahatani bawang merah dengan sistem pemasaran tebasan ini menunjukkan total biaya produksi usahatani bawang merah Rp.88.109.666,7/Ha, total penerimaan usahatani bawang merah Rp. 128.313.365/Ha, dengan pendapatan senilai Rp. 40.203.698/Ha. R/C Ratio sebesar 1,46 serta rentabilitas 15,2%.